Analisis Marketing Strategy JYP Entertainment ke Amerika Serikat: Studi Kasus Album “Ready To Be” Twice 2023 - Chelsi Okmelita Purnomo; Nadia Aulia Rachma; Resa Rasyidah (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze JYP Entertainment’s implementation of music album marketing strategies in entering the U.S. market through the group TWICE. In 2020, according to a Billboard report, JYP Entertainment entered into a strategic partnership with Republic Records. TWICE achieved the highest sales record for a female K-pop idol group and received numerous awards. The research method used in this study is descriptive. Research data was obtained from secondary sources, specifically literature reviews and articles on news portals and official websites, which were then analyzed to answer the research questions. The analysis technique applied is qualitative. The research question in this study focuses on the following: “How does JYP Entertainment’s marketing strategy market TWICE’s ‘Ready To Be 2023’ album to the United States?” To answer the research question, this study uses a framework of standardization and adaptation within the 4Ps of the marketing mix (Product, Place, Promotion, Price). Using the 4P framework, JYP Entertainment demonstrates the implementation of product standardization and adaptation specific to the United States, such as limited-edition products and digital versions, physical album distribution through U.S. platforms, various promotions conducted in the United States—such as the iconic light display on the Empire State Building—and price adjustments accounting for sales tax in each platform.